Monetary Policy and Foreign Denominated Debt by Non-Bank Borrowers - Joscha Beckmann; Robert Czudaj; Thomas Osowski (Credit and Capital Markets – Kredit und Kapital, 2021)
This paper analyzes cross border credit from a new perspective: We assess globally aggregated foreign-denominated credit to non-bank borrowers (provided by the BIS) and analyze which factors drive debt denominated in yen, euro and US dollar between 2003 and 2020. The determinants we analyze include global economic activity, global commodity prices and the evolution of assets in the FED balance sheet. We also consider assets in the ECB and the BOJ Balance in a second step. Our results show that global economic activity is the main driver of dollar debt only before the financial crisis while the Fed balance sheet drives dollar debt afterwards. We also identify a crowding-out effect of FED balance activities on debt denominated in yen and euro. On the other hand, effects of changes in the ECB and BOJ balance are qualitatively less important and more stable.
Keywords: C32; E31; E58; F42; 330; global liquidity; debt; VAR models